How to improve performance in public investment projects - Pereira, L.; Dias, Á.; Costa, R. L.; Gonçalves, R. (International Journal of Procurement Management, 2022)
The objective of this research work is to understand and identify the main cause failures and errors of public investment projects, which lead to significant deviations from the values estimated in economic studies and to propose solutions to prevent it in the future. This research conducted in Portugal has as a sample of dozens of investment projects that were executed in the last 20 years. The main findings indicate that the factors that explain the low performance of the project are the adoption of non-validated assumptions, the lack of risk analysis, and the insufficient qualifications of the project evaluators. Considering the contributions the main suggestion are the existence of a preventive entity to evaluate, analyses and assess in an independent way social and economic return on investment for the society and for the shareholders.